CHALLENGES FACING MOTOR VEHICLE INSURANCE INDUSTRY IN KENYA - Kajwang, Ben (International Journal of Strategic Management, 2022)
Purpose: The study examined the challenges facing the motor vehicle insurance industry in Kenya. Methodology: This study employed a systematic literature review of previous studies on motor vehicle insurance industry with an inclusion criteria of studies not over fear years old. Relevant seminal references and journal articles for the study were also identified using Google Scholar. This research method was preferred in this study since it is reliable and saves on time and resources as compared to primary data collection methods. Findings: From the review of the previous researches, the study found that the motor insurance industry experiences a variety of challenges that affects its growth and sustainability. These challenges range from security, financial, technical, legal and regulatory challenges. The measures put in place to mitigate these challenges were found to be inadequate and requires more effort by the motor insurance industry to work with other entities such as local businesses, vehicle manufacturing companies and the government. The regulatory policies enforced by the regulatory authorities of Kenya were found to have a significant influence on the performance of the motor insurance industry in Kenya. Unique contribution to Theory, Practice and Policy: The study recommended that the motor insurance industry should invest in innovative technologies such as telematics which can be used in the calculation of premium so as to offer their customers affordable premium prices. The management of the motor insurance companies should invest in new marketing strategies that will improve their customer service delivery especially in the insurance claiming processes. The study also recommended that the IRA should implement better regulation policies that will promote easy adoption of the innovate technologies in the motor insurance industry. This study will be relevant to the key stakeholders in the motor insurance industry. The management of the motor insurance companies will have a wider scope of knowledge on other challenges that they may have not experienced and the measures that have been used to mitigate such challenges. The findings from this study may be helpful to the insurance regulatory authority as they implement policies to accelerate the growth of the insurance business in Kenya. The study will also provide a good literature base for researchers and scholars on studies regarding motor insurance industry since they are still scant.